The psychometric properties of the Swahili version of the Primary Care Post Traumatic Stress Disorder screen for DSM-5 among adults in Kenya - Mwangala, Patrick N.; Guni, Joseph Newton; Mwangi, Paul; Makandi, Millicent; Kerubo, Anita; Odhiambo, Rachel; Abubakar, Amina (Frontiers in Psychiatry, 2024)
Background: The psychometric properties of the Primary Care PTSD Screen for DSM-5 (PC-PTSD-5) are undocumented in Kenya and sub-Saharan Africa (SSA) at large. This study aimed to evaluate the psychometric properties of the Swahili version of the tool, S-PC-PTSD-5, in a community sample of adults 18 years and older drawn from Nairobi, Mombasa and Kwale counties in Kenya. Methods: Analysis of cross-sectional data from 1431 adults from the community was conducted, examining the reliability, factorial structure, measurement invariance, and convergent and divergent validity of the interviewer-administered S-PC-PTSD-5. Results: Out of 1431 adults who completed the S-PC-PTSD-5, 666 (46.5%) reported experiencing at least one traumatic event. Internal consistency of the S-PC-PTSD-5 was good overall, with alpha and omega values above 0.7. Confirmatory factor analysis (CFA) results indicated a one-factor structure of the S-PC-PTSD-5 for the overall sample. Multigroup CFA also demonstrated factorial invariance for sex for the one-factor structure of S-PC-PTSD-5. Scores for S-PC-PTSD-5 significantly correlated (positively) with those of generalized anxiety disorder (GAD7) and depressive symptoms (PHQ9), indicating convergent validity. S-PC-PTSD-5 scores also significantly correlated (negatively) with the WHO-5 wellbeing index, supporting divergent validity. Conclusions: The S-PC-PTSD-5 is a reliable and valid unidimensional measure. It appears to be a valuable screening measure for probable PTSD in both urban and rural community settings in Kenya. Nonetheless, to confidently identify those who may need treatment/additional support, further research on the reliability and validity of S-PC-PTSD-5 is required, especially its diagnostic accuracy at different cutoff scores.